Process modeling and comparison study of acid gas removal unit by using different aqueous amines - Sanggie, Florence Wednna (2011)
Natural gas need to be purified to meet the quality standards since it contains impurities such as carbon dioxide (CO2) and hydrogen sulfide (H2S), which are they are the main acid gases that as its can cause corrosion, reduce the heating and sales value of gas. Aqueous amine solutions are proven to be practical solvents for the treatment of natural gas. By simply changing their amine solutions, many inefficient acid gas removal units can be optimized. Acid gas removal unit (AGRU) simulation is an essential tool for control and operations in gas processing plant because it can be used to stimulate and analyses the under different operating conditions.In this study, Monoethanolamine (MEA), Dietanolamine (DEA) and Methyldiethanolamine (MDEA) will be use to model the acid gas removal unit process by using Aspen Hysys. MEA is effective at removing almost all hydrogen sulfide and carbon dioxide among the other amines. Meanwhile, DEA and MDEA allows for some carbon dioxide to be left in the sweet gas that are suit for gas steams with less stringent product specifications. Accordingly, the heat consumption at the regenerator was in the following order MEA >DEA > MDEA. Improvement studies were extended to the effect of increasing the circulation rate, amines concentration and reboiler heat consumption. By increasing the circulation rate, MEA causes the CO2 to be almost completely absorbed in the column even at the lowest low circulation rate followed by DEA and. MDEA. By increasing concentration of amine, MEA and MDEA showed at 15 wt % or greater is required to achieve the specified acid gas removal and 25 wt % for DEA. One also can reduce heat of reaction by changing from a primary to secondary amine which both gives almost the same acid gas removal efficiency. This research can broaden by using different simulation tools available model the AGRU and also perform the comparison on the cost estimating for MEA, DEA and MDEA.